A Clinical Librarian Embedded in Medical Education: Patient-Centered Encounters for Preclinical Medical Students. Issue 1 (2nd January 2018) - Blake, Lindsay; Yang, Frances M.; Brandon, Hutton; Wilson, Benjamin; Page, Renee
ABSTRACT: Adding patient encounters and simulation to the preclinical years of medical school is becoming increasingly popular. This article describes the creation of active learning opportunities by a clinical librarian that are aimed at training preclinical students through the use of simulated patient scenarios. Scenarios for second-year students walk them through the evidence-based resources needed in clinical years and beyond through a standardized patient encounter. Scenarios for first-year students involve role-play of cases where the patient and physician bring contrasting ideas to the outpatient interaction. All scenarios are carried out under the guidance of a clinician and librarian.